Development of Electronic Textbook for Accounting Learning Evaluation Course - Hakim, Luqman; Wahjudi, Eko; Widayati, Irin; Pratiwi, Vivi; Retnosari, Dyah Silvian; Rafsanjani, Mohamad Arief (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2023)
This study aims to examine the process of developing electronic textbooks for accounting learning evaluation courses to improve the quality of learning in accounting education study programs. The study followed Research and Development (R & D) with the ADDIE model (analysis, design, development, implementation, and evaluation). The students of the accounting education program at Universitas Negeri Surabaya were involved in this research. The findings indicated that electronic textbooks for accounting learning obtained very good responses with very appropriate interpretation criteria according to students’ needs. For this matter, this product is expected to be an alternative teaching material for students to enhance material understanding, learning independence, and learning motivation in the online course process of accounting learning evaluation